Differential Effect of Retroactive Interference on Object and Spatial Memory in the Course of Healthy Aging and Neurodegeneration - Muecke, Hannah; Richter, Nils; von Reutern, Boris; Kukolja, Juraj; Fink, Gereon R.; Onur, Oezguer A. (Frontiers in Aging Neuroscience, 2018)
Objective: In subjects with mild cognitive impairment (MCI), interference during memory consolidation may further degrade subsequent recall of newly learned information. We investigated whether spatial and object memory are differentially susceptible to interference. Method: Thirty-nine healthy young subjects, thirty-nine healthy older subjects, and twelve subjects suffering from mild cognitive impairment encoded objects and their spatial position on a 4-by-5 grid. Encoding was followed by either i) a pause, ii) an interference task immediately following encoding, or iii) an interference task following encoding after a six minute delay. Type of interference (no, early, delayed) was applied in different sessions and order was counterbalanced. Twelve minutes after encoding, subjects saw objects previously presented or new ones. Subjects indicated whether they recognized the object, and if so, the objects’ position during encoding. Results: Interference during consolidation provoked a negative effect on spatial memory in young more than older controls. In MCI, object but not spatial memory was affected by interference. Furthermore, a shift from fine- to coarse-grained spatial representation was observed in MCI. No differential effect of early versus late interference in either of the groups was detected. Conclusions: Data show that consolidation in healthy aging and MCI differs from consolidation in young controls. Data suggest differential processes underlying object and spatial memory and that these are differentially affected by aging and MCI.